Analisis Efisiensi Usaha Pembesaran Ikan Nila di Desa Marga Sakti Kecamatan Padang Jaya Kabupaten Bengkulu Utara - Cahyati, Ainun; Yuristia, Rahmi; Sumantri, Bambang (LPPM Universitas Malikussaleh - Indonesia, 2022)
North Bengkulu Regency is one of the freshwater fishery producing areas in Indonesia Bengkulu Province. Forty percent of Bengkulu Province's total freshwater fish production is from North Bengkulu. The fishery center in North Bengkulu is in the District of Padang Jaya and has been designated as a freshwater fishery Minapolitan area. Type Tilapia (Oreochromis niloticus) is one type of fish that is in great demand by the community to be cultivated, because Tilapia has sufficient tolerance high relative to the environment as well as its relatively fast growth. Purpose This research is: (1) Analyzing the amount of business income Tilapia and, (2) Analyzing the efficiency level of Tilapia rearing business. Determination of the location in this research was conducted intentionally (purposive). The population in this field study is tilapia farmers totaling 150 farmers. Determination of the number of respondents in the field study This is the Simple Random Sampling method. The average value of Tilapia fish production in Marga Sakti Village is 1.817 Kg/MT so that the total revenue received by farmers Tilapia an average of Rp. 33.608.333/ MT and the value of fish farmers' income The average tilapia in Marga Sakti Village is Rp. 18,192,229/MT. So that the value of The average R/C ratio per stocking season is 2.28. This shows that the effort Tilapia cultivation with a calm water pond system in Marga Sakti Village is categorized as suitable for cultivation cultivated because the amount of expenditure on cultivation business costs is smaller than with acceptance.